Biogenic amine profile in unfermented and fermented orange industrial waste - Pereira-Vasques, Milene Stefani [UNESP]; Nunes, Aline [UNESP]; Monteiro, Gean Charles [UNESP]; Fleuri, Luciana Francisco [UNESP]; Lima, Giuseppina Pace Pereira [UNESP] (Elsevier, 2025)
This study investigates the biogenic amine, precursor amino acids and their derivatives profiles of industrial orange waste, both in its unfermented form and after fermentation using solid-state fermentation (SSF) with different Aspergillus species. The research identifies the presence of various biogenic amines, such as serotonin, dopamine, histamine, and tyramine, as well as precursor amino acids and their derivatives including L-tryptophan. Fermentation with A. niger and A. oryzae significantly increased the concentrations of serotonin and L-tryptophan and promoted the production of agmatine using bagasse as a substrate. Bagasse, which contain no agmatine yielded substantial amounts following fermentation with A. niger and A. oryzae. Additionally, the concentration of tyramine -a biogenic amine that can be hazardous in large quantities -decreased in the peel and frit after SSF, suggesting potential applications in the food, pharmaceutical, and cosmetic industries. This study presents the first comprehensive analysis of biogenic amines in orange waste, highlighting its potential for valorization in industrial processes.